Gradualism, bifurcation and fading qualia. - Sebastián, Miguel Ángel; Martínez, Manolo (Analysis, 2024)
When reasoning about dependence relations, philosophers often rely on gradualist assumptions, according to which abrupt changes in a phenomenon of interest can result only from abrupt changes in the low-level phenomena on which it depends. These assumptions, while strictly correct if the dependence relation in question can be expressed by continuous dynamical equations, should be handled with care: very often the descriptively relevant property of a dynamical system connecting high- and low-level phenomena is not its instantaneous behaviour but its stable fixed points (those in the vicinity of which it spends most of the time, after comparatively short transitory periods), and stable fixed points can change abruptly as a result of infinitesimal changes of the low-level phenomenon. We illustrate this potential gradualist trap by showing that Chalmers' fading qualia argument falls into it.